Tax control procedures for revalued real estate transactions - an applied study- - idrissi, Moulay Lakhdar; Bessas , Ahmed (Journal of Excellence for Economics and Management Research, 2025)
This study aims to understand the purpose of real estate transactions, their components, and the basis on which they are re-evaluated by the tax administration. It also identifies the tax control method involved in the real estate settlement process. The study lists the various violations that may occur in real estate transactions and how to address them using several deterrent methods, provided that the provisions of Article 38 bis 2 of the Tax Procedures Law are adhered to. Any violation of these provisions may result in the control being invalidated. The most important recommendations emphasized the need to review the registration fee rate by reducing it, thus allowing taxpayers in this category to avoid resorting to breaching tax obligations.